Progress in question: the temporalities of politics, support and belonging in gender- and sexually-diverse pedagogies. Issue 6 (2nd November 2017) - Cover, Rob; Rasmussen, Mary Lou; Aggleton, Peter; Marshall, Daniel
Abstract: In this paper, we examine some of the ways in which different approaches to the idea of progress emerge alongside competing temporalities of sexual and gender diversity and belonging in the context of public debates and discussions on the Safe Schools Coalition review (February 2016). The public debates provided an important point-of-focus for understanding the contemporary setting of support for minorities in relation to cultural belonging and inclusivity in educational settings. The paper discusses the relationship between progress and temporality in its historical setting within Australian LGBTQ political history. We investigate three angles in which progress has been articulated in the Safe Schools debates: (1) disruptions to support as political setback to progress; (2) the view that safe support is necessary for the progress of LGBTQ 'vulnerable' youth within 'developmental stages'; (c) the framing by conservative commentators that LGBTQ support curricula is a form of 'progressive politics' that undoes normative histories of neoliberal and conservative progress. Making use of the public debates around the Safe Schools curriculum to critique some of the ways in which progress on minority belonging for younger persons helps open the fields of meaning for alternative kinds of belonging that are produced through alternative cultural histories of marginalized subjects.